Long Non-coding RNA N1LR Protects Against Myocardial Ischemic/Reperfusion Injury Through Regulating the TGF-β Signaling Pathway - Du, Lin; Chen, Jie; Wu, Yong; Xia, Guangwei; Chen, Mingxing; Zhao, Pei; Wang, Yao; Yao, Deshan; Liu, Fan; Zhang, Lina; Wang, Xue; Yang, Yi; et al. (Frontiers in Cardiovascular Medicine, 2021)
The mechanism oflong non-coding RNAs (LncRNAs) in acute myocardial infarction (AMI)is not fully understood. Previous studies showed that lncRNA N1LR was down-regulated in ischemiccerebral stroke and its up-regulation was protective.This study was designed to confirm the protectiveeffect and further to explore the potential mechanismof N1LR in ischemic/reperfusion (I/R) injury after AMI.Male C57BL/6J mice and H9c2 cardiomyocytes were selected to constructinvivo and cellularpathological models. In the cellular study, N1LR expressionwas markedly decreased by H2O2 and Cocl2 treatments which mimic I/R effectin cardiomyocytes, andoverexpression of N1LR alleviate the apoptosis, inflammation reaction and LDH release in cardiomyocytes treated with H2O2 and Cocl2.In vivo studyshowed that overexpression of N1LR enhanced cardiac functionand suppressed inflammatory response and fibrosis. Mechanistically, we found that the expression of TGF-β1, Col1a1, Col3a1and α-SMA wasdecreased in N1LR overexpression group exposed toH2O2 and Cocl2.All the results suggested thatN1LRoverexpresion can be a cardiac protection against ischemic reperfusion injury in vivo and vitro, a mechanismthat may involveTGF-β pathway.